Investigasi Perilaku Compulsive Buying Berdasarkan Pembayaran NonTunai, Lingkungan Sosial, dan Kondisi Keuangan - Berto Mulia Wibawa; Malvin Piero; Ribka Anintha Miyagi (Institut Teknologi Sepuluh Nopember, 2020)
The behavior of people living in Surabaya is different from people from othercities, including the shopping behavior of the students in Surabaya. Students inSurabaya have more temptation to behave negatively in shopping. Itencourages the occurrence of irregularities in shopping. Such action isclassified as compulsive buying. Compulsive buying is a spending behaviorbased on a strong desire that makes people lose consciousness and can notcontrol themself. This study aims to analyze the effect of sales promotion,cashless payment, social environment, and financial condition on compulsivebuying on university students in Surabaya. The method used is descriptiveanalysis with multiple cross-sectional designs. Data were analyzed withStructural Equation Modeling. The result of this research showed that salespromotion, cashless payment, and financial condition variables have a positiveeffect on compulsive behavior on university students in Surabaya.